Factors affecting youth bankrupty in Malaysia - F., Diana-Rose; Mohd Ashhari, Zariyawati (Perpustakaan Sultan Abdul Samad, Universiti Putra Malaysia, 2015)
The aim of this study is to determine factors affecting youth bankruptcy in Malaysia.This study provides theoretical evidences that will benefit the financial institutions in the improvement of borrowing and lending by avoiding excessive debt among customers. In addition, it will expand the current knowledge and increase awareness of bankruptcy among youth. Thus, this research paper pursues two objectives: to provide a statistical profile of youth bankruptcy and to investigate factors affecting youth bankruptcy in Malaysia. An overview of statistical youth filing for bankruptcy was acquired from the Malaysia Department of Insolvency (MDI). The interviews were performed and questionnaires were distributed to 140 individual who filed for bankruptcy in the Malaysia Department of Insolvency (MDI) and Credit Counseling and Debt Management Agency (AKPK). There are seven hypotheses used in testing study aspects, namely gender, race, education, marital status, occupation, work experience, and loans. Hence, result of regression analysis shows that six out of seven variables are significant to the dependent variable. The lack of discipline regarding financial management is why many youth in Malaysians today carry major debts and face a high probability of going bankrupt.